Software testing; concepts and practices - Mustafa,K (Narosa, 2012)
Focusing on software testing in practice, this book has been planned to suit the needs of both the practitioner and the academician. It includes concepts of software testing that have been modeled as a phase-embedded activity rather than treating them as separate and post development activity.